Characterization of horse gram accessions on the basis of morphological and biochemical characters - P. DIVYA; K. KANAKA DURGA; N. SUNIL; M. RAJASRIP; RAZIA SULTANA; K. KESHAVULU (Seed Research, 2026)
Fifty horse gram accessions were characterized based on the morphological characters viz., plant growth pattern, plant growth habit, stem color, leaf color and seed color. Significant correlation was noticed among the qualitative traits, while biochemical parameters exhibited positive and negative relationship with the morphological qualitative traits, but the relationship was non-significant. Plant growth pattern was significantly and positively correlated with plant growth habit and leaf color, while was significant negative relationship was noticed between plant growth pattern and stem color. Plant growth habit showed significant negative relationship with stem color and significant positive relationship with leaf color. However, biochemical parameters viz., proteins and phenols exhibited positive and negative relationship with the morphological qualitative traits, but the relationship was non-significant.